Assessment of Nurses Responsibilities in Integrated Management of Chronically Ill Patients. - Chiejina, Edith N.; Anieche, John E. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Primary care of the chronically ill is based on multiprofessional teams. However, each professional group has its own peculiar input to the team work. This study assessed the responsibilities of nurses in integrated management of chronically ill patients. Purposive sampling technique was used to select 240 nurses working in secondary and tertiary health institutions in Anambra State of Nigeria. Three research questions and two null hypotheses guided the study. The instrument used for data collection was questionnaire on Nursing Interventions in Integrated Management of Chronically ill Patients. Standard descriptive statistics was used to summarize the variables. Mean score and percentages were used to answer the research questions while Pearson Product Moment correlation was adopted in testing the null hypotheses at 0.01 level of significant. Findings from the study indicated high levels of optimization of clients’ therapy (mean=2.9806) and nursing audit (mean=2.9033), and high levels of nurses collaboration with majority of the practice team in their integrated care of chronically ill clients. Significant relationships were also found to exist between nursing audit and follow-up of the clients, and also between nursing audit and the interactions among the practice team.